1989
DOI: 10.3168/jds.s0022-0302(89)79444-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Somatotropin-Releasing Factor and Photoperiods on Carcass Parameters and Mammary Gland Development of Dairy Heifers

Abstract: Forty-eight heifers (3 mo old) were subjected for 35 wk to twice daily s.c. injections of saline or human somatotropin-releasing factor (5 microgram.kg-1 BW) and photoperiod of 8 h (short day) or 16 h (long day) of light daily according to a 2 X 2 factorial design. There was no treatment effect on slaughter weight, withers height, and carcass length. Somatotropin-releasing factor increased thymus weight, metacarpal length, and protein content of the carcass but decreased carcass fat content. Long day photoperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A long-day photoperiod (16 v. 8 h of daylight) increased mammary parenchymal weight by 40% in peri-pubertal heifer and by 30% in post-pubertal heifer (Petitclerc et al, 1985). Such an exposure also increased lean growth (Petitclerc et al, 1985;Ringuet et al, 1989). Only one study reported the effect of pre-pubertal photoperiod on milk production.…”
Section: Nutritional Factorsmentioning
confidence: 98%
“…A long-day photoperiod (16 v. 8 h of daylight) increased mammary parenchymal weight by 40% in peri-pubertal heifer and by 30% in post-pubertal heifer (Petitclerc et al, 1985). Such an exposure also increased lean growth (Petitclerc et al, 1985;Ringuet et al, 1989). Only one study reported the effect of pre-pubertal photoperiod on milk production.…”
Section: Nutritional Factorsmentioning
confidence: 98%
“…Hence, milk production is a function of alveolar cell number and of the metabolic activity of these cells along with the metabolic support provided by other body tissues. Previously published results have reported either no change (Purup et al 1993) or an increase (Sandles et al 1987;Ringuet et al 1989) in mammary parenchyma of peripubertal heifers receiving GH or GRF. Increases in parenchymal protein (Purup et al 1993) and in total parenchymal DNA (Sandles et al 1987) have also been observed in GH-treated heifers.…”
Section: Farmer Et Al -Grf and Mammary Gland Development 337mentioning
confidence: 96%
“…This decrease was brought about by a diminished feed intake which was significant during the 4th wk of lactation in LACT and GEST-LACT sows (Farmer et al 1992). A decrease in extraparenchymal tissue was also reported in GH-treated (Sandles et al 1987;Purup et al 1993) and in GRF-injected prepubertal heifers (Ringuet et al 1989) and was said to be due to the lypolytic action of GH. For personal use only.…”
Section: Farmer Et Al -Grf and Mammary Gland Development 337mentioning
confidence: 98%
See 1 more Smart Citation
“…In cattle, most early work with exogenous GRF showed no effect on growth (Plouzek et al, 1988;Ringuet et al, 1989;Lapierre et al, 1991), feed intake (Plouzek et al, 1988;Lapierre et al, 1991), feed efficiency (Lapierre et al, 1991) or diet digestibility (Moseley et al, 1987;Plouzek et al, 1988). However, improvements in nitrogen (N) retention (Moseley et al, 1987;Lapierre et al, 1991) and apparent digestibility of dry matter (DM) and N (Lapierre et al, 1991) were reported and subsequently confirmed by Lapierre et al (1992) using a higher dose of GRF.…”
Section: Introductionmentioning
confidence: 92%